2023
DOI: 10.1111/1365-2745.14154
|View full text |Cite
|
Sign up to set email alerts
|

Increasing plant species richness by seeding has marginal effects on ecosystem functioning in agricultural grasslands

Abstract: Experimental evidence shows that grassland plant diversity enhances ecosystem functioning. Yet, the transfer of results from controlled biodiversity experiments to naturally assembled ‘real world’ ecosystems remains challenging due to environmental variation among sites, confounding biodiversity ecosystem functioning relations in observational studies. To bridge the gap between classical biodiversity‐ecosystem functioning experiments and observational studies of naturally assembled and managed ecosystems, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…This results from a combination of the yield reduction, which indicates that each added species increases the chance of including a species with lower yields than previously included species (Roscher et al, 2005), and the saturation curve that indicates that similarities in occupied ecological niches between species increase and reduce the yield gain from each additional species (Lüscher et al, 2022; Tilman et al, 1997). The saturation of ecological niches occurs with comparably few species in productive grasslands, compared to semi‐natural grasslands (Freitag et al, 2023).…”
Section: Considerations For the Successful Implementation Of Grasslan...mentioning
confidence: 99%
“…This results from a combination of the yield reduction, which indicates that each added species increases the chance of including a species with lower yields than previously included species (Roscher et al, 2005), and the saturation curve that indicates that similarities in occupied ecological niches between species increase and reduce the yield gain from each additional species (Lüscher et al, 2022; Tilman et al, 1997). The saturation of ecological niches occurs with comparably few species in productive grasslands, compared to semi‐natural grasslands (Freitag et al, 2023).…”
Section: Considerations For the Successful Implementation Of Grasslan...mentioning
confidence: 99%
“…We identify four possible explanations. First, BEF-relationships are often asymptotic in grassland experiments 50 , with biomass gains levelling off when richness levels exceed approximately 10 species, possibly due to a saturation in resource use 8,51 . Only 8.7% of our managed grassland plots had less than 10 species, making them more diverse than most grassland communities in biodiversity experiments 52 .…”
Section: Richnessmentioning
confidence: 99%
“…2). This was done by scarifying the reduced land-use + seed addition plot, whereby scarifying is a minor manual mechanical disturbance of the top soil surface down to 5 cm using lawn scarifier to increase seedling establishment by promoting seed-soil contact as well as by reducing light competition 37,48,49,51 , and then sowing new species (twice: in autumn 2019 and spring 2020, ranging from 40 to 74 species depending on deviance of the species pool at the site to the regional species pool). In the Schorfheide-Chorin region, only species originally absent in the plot (but present in the region) were sown, while in Hainich-Dün and the Schwäbische Alb, in addition to new species, unintentionally also species already present at the site were sown.…”
Section: Experimental Designmentioning
confidence: 99%
“…Some of the previous studies on plant diversity and productivity (biodiversity experiments) showed that species-rich grassland communities are associated with high-level delivery of aboveground biomass (Hector et al, 1999). However, these relationships are less established and still under-debated under more realistic grassland management conditions (Freitag et al, 2023). More recent studies have focused on the diversity of the functional traits of different plant species within the grassland plant community (de Bello et al, 2010;Gross et al, 2017).…”
Section: Introductionmentioning
confidence: 99%